Podnikatelský záměr pro založení firmy - Dejmková, Lenka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Práce vznikla na základě reálného problému týkajícího se založení podniku působícího v oblasti balící techniky průmyslových výrobků. Na základě zjištěných poznatků z analýz vnějšího a vnitřního prostředí je navrhováno vhodné řešení podnikatelského záměru firmy, což je cílem této práce.

This thesis was elaborated on the basis of a real problem related to an establishment of the company producing packaging facilities for technical products. The aim of the thesis is to develop and propose an appropriate business solution, based on the results of external and internal business environment analysis.
Business Plan for the Enterprise Establishment
Keywords: Podnikatelský záměr; podnik; založení podniku; balení průmyslových výrobků; finanční plán; marketingový plán; organizační plán; analýza rizik; Business plan; enterprise; enterprise establishment; packaging of industrial products; financial plan; marketing plan; organizational plan; risk analysis